Public commemoration in service of nation, state and dynastic identity-building - Marković Anita (Nasleđe)
This paper deals with the analysis of public festivities organized in Belgrade on the occasion of the centenary of the beginning of the First Serbian Uprising, and their role in the construction of national, state and dynastic identity. Celebrations of jubilees and anniversaries can be seen as a special type of public festivity; often-solemn commemorations of certain events or personalities organized in certain years. Their commemorative nature also has the potential for them to be powerful propaganda tools in the construction of national, state and dynastic identities. When considering the socio-political situation at the time of the centenary of the First Serbian Uprising in 1804 in the country, largely metered by the dynastic change of 1903, the organization of the commemoration of this anniversary as an official state ceremony - the highlight of this being the coronation of Petar Karađorđević - necessitated, in the form of an ephemeral spectacle, the symbolic revival, reinterpretation and reconstruction of the past, in order to emphasize the legitimacy of the power of the new ruler and dynasty and to encourage promotion of this in a broad range of media.